An energy dissipation-based fatigue crack growth model. (September 2018) - Wang, X.G.; Ran, H.R.; Jiang, C.; Fang, Q.H.
Graphical abstract: Highlights: An energy dissipation-based fatigue crack growth rate model is established. Thermography is applied to estimate the dissipated energy at the crack tip zone. Energy dissipation rate increases exponentially with the stress-intensity range. Stress-ratio-dependence of the proposed fatigue crack growth model is proofed. An effective energy dissipation rate is proposed by considering the crack closure. Abstract: This paper presents a local approach to analyze the fatigue crack growth rate (FCGR) through the characterization on the dissipative process of fatigue crack tip zone. An energy dissipation-based FCGR model is established, and a dedicated thermographic method for dissipated energy assessment in the cyclic plastic zone is developed. Fatigue crack growth tests are conducted on the 316L steel under the varied stress ratios. The results demonstrate that the fatigue crack growth process can be well characterized by the near-tip energy dissipation. The proposed FCGR model shows, however, an unexpected stress-ratio-dependence. This dependence is analyzed by the crack closure effect, and the FCGR model is improved by introducing an effective energy dissipation rate concept.